Fruit productivity of Stone pine (Pinus pinea L.) along a climatic gradient in Chile - Loewe Muñoz, V. (2016)
Pinus pinea L. is a Mediterranean species of economic importance due to its edible seeds, the pine nuts that have high market value. We analyzed fruit productivity by recording cone number per tree (CN) on 3464 trees distributed along a climatic gradient in Chile. Cone weight at harvest (CW) and in-shell pine nut number per cone (IS) were measured on 76 superior trees. Climatic and biometeorological variables, defined based on 11 physio-phenological reproductive phases, were related to fruit production traits. Results showed marked differences among North, South and Dry coast areas. The highest values of cone productivity (32 kg tree-1) and CN (62 cones tree-1) were recorded in the South. Stone pine cone production throughout Chile was favored by spring minimum temperature above 7 °C; annual thermal oscillation below 12 °C and late summer temperature below 6 °C during differentiation of reproductive shoots; and a high spring rainfall, except during male flowering period. Accumulated rainfall above 14 mm during 2 year-old conelet growth produced heavier cones. IS significantly increased when accumulated rainfall during cone ripening was above 133 mm. Therefore, water supply would be recommended as a cultural practice to mitigate the negative impact of reduced water availability on fruit productivity.